PENGARUH KEBERADAAN DEWAN PENGAWASAN, FORMALISASI PENGEMBANGAN, KETERLIBATAN PEMAKAI, KEMAMPUAN TEKNIK PERSONALIA DAN LOKASI DEPARTEMEN TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI PADA BANK UMUM DI KOTA SEMARANG - Anggun Prasetia Ningtyas, 12.05.52.0136; Srimindarti, Ceacilia (Students Journal of Accounting and Banking, 2016)
The population in this study were employees working at commercial banks in the city of Semarang. The sample in this study is the accounting information system and the sample size of 100 respondents. The results showed that the presence of the board of supervision, the involvement of users and engineering capabilities personnel significant positive effect on the performance of the performance of the accounting information system. The formalization of the positive development was not significant to the performance of accounting and information systems department Location negative not significant to the performance of the accounting information system.Keywords: Presence Control Board, A Formalization of Development, User Involvement, Capability Engineering Personnel Location and Performan Department of Accounting Information Syste